2009
DOI: 10.1185/03007990903136378
|View full text |Cite
|
Sign up to set email alerts
|

Assessing incidence and economic burden of genital warts with data from a US commercially insured population

Abstract: Genital warts represent a significant health and cost burden in the US. Adoption of novel healthcare technologies such as vaccines along with traditional interventions such as physician education of signs and symptoms, condom use and abstinence or limiting number of sexual partners may significantly help reduce the burden of genital warts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 36 publications
9
52
2
2
Order By: Relevance
“…Our findings are similar to incidence estimates from studies using private health insurance claims that reported GW incidence rates of 1.70 [11], 1.62 [12], and 1.10 [13] cases per 1000 person-years. Those studies also observed the highest GW incidence among younger men.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our findings are similar to incidence estimates from studies using private health insurance claims that reported GW incidence rates of 1.70 [11], 1.62 [12], and 1.10 [13] cases per 1000 person-years. Those studies also observed the highest GW incidence among younger men.…”
Section: Discussionsupporting
confidence: 88%
“…Misclassification could partially explain why men with genital HPV infections with only oncogenic types had the longest time from infection to lesion development. Because our GW incidence rates are similar to those found in previous studies [11,12,13], it is unlikely that there was extensive misclassification. The generalizability of our findings may also be limited, because men who agree to participate in a 4-year study are likely to not be representative of the underlying population at each study site.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations